Host–parasite interactions that guide red blood cell invasion by malaria parasites. Issue 3 (May 2015) - Paul, Aditya S.; Egan, Elizabeth S.; Duraisingh, Manoj T.
<x xml:space="preserve">Abstract</x> Purpose of review Malaria is caused by the infection and proliferation of parasites from the genus Plasmodium in red blood cells (RBCs). A free Plasmodium parasite, or merozoite, released from an infected RBC must invade another RBC host cell to sustain a blood-stage infection. Here, we review recent advances on RBC invasion by Plasmodium merozoites, focusing on specific molecular interactions between host and parasite. Recent findings Recent work highlights the central role of host–parasite interactions at virtually every stage of RBC invasion by merozoites. Biophysical experiments have for the first time measured the strength of merozoite–RBC attachment during invasion. For P. falciparum, there have been many key insights regarding the invasion ligand PfRh5 in particular, including its influence on host species tropism, a co-crystal structure with its RBC receptor basigin, and its suitability as a vaccine target. For P. vivax, researchers identified the origin and emergence of the parasite from Africa, demonstrating a natural link to the Duffy-negative RBC variant in African populations. For the simian parasite P. knowlesi, zoonotic invasion into human cells is linked to RBC age, which has implications for parasitemia during an infection and thus malaria. Summary New studies of the molecular and cellular mechanisms governing RBC invasion by Plasmodium parasites have shed light on various aspects of parasite biology and host cell tropism, and indicate opportunities for malaria control.